Flowchart and Algorithm Basics: The Art of Programming - Chaudhuri, A. B (Mercury Learning & Information, 2020)
Including applied and illustrative examples from different subject areas, this book aims to equip readers with all the best, most efficient, and well-structured programming logic in the form of flowcharts and algorithms. --